2015
DOI: 10.15408/a.v2i2.2090
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Tema Dalam Buku Al-Qira'ah Ar-Rasyidah Untuk Pelatihan Menulis Kreatif Bahasa Arab

Abstract: Developing theme in a text of Arabic reading is the basis in a creative writing. By understanding the pattern of theme development in a text, beginner who wants to write in Arabic is easier in arranging the idea. This article is a research to see a great correlation between thematic progression with the creative writing in Arabic. The book taken as sample was al-Qira� 'ah al-Ra� syidah which is used in MAN Karang Anyar and MAN 1 Surakarta. Related to the rheme in developing the theme, the students of both scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…(Mulyani, 2016) Third, exploring the linguistic side of a text. (Anis, Arifuddin, & Farhah, 2015;Roviin, 2018) This is shown in a study of the concept of symbols in the al-Barzanji 248 VOL. 9 NO.…”
Section: Introductionmentioning
confidence: 94%
“…(Mulyani, 2016) Third, exploring the linguistic side of a text. (Anis, Arifuddin, & Farhah, 2015;Roviin, 2018) This is shown in a study of the concept of symbols in the al-Barzanji 248 VOL. 9 NO.…”
Section: Introductionmentioning
confidence: 94%
“…Theme signalizes the entities which are already known beforehand while Rheme signalizes the new elements contained in the information. Anis (2015) emphasizes that in Arabic texts, the Theme and Rheme can be developed in certain patterns (thematic progression patterns). Anis (2018) outlines and compares the constructions of Theme and Rheme in the Arabic and Javanese languages.…”
Section: Introductionmentioning
confidence: 99%
“…In his research, Anis (2014:245) had concluded that jumlah ismiyyah (Arabic Nominal Sentences) was Daily Newspaper. Except, in the imperative sentences, the headline was using the verbal sentences [1,2]. In this case, to make an understandable way to elaborate both of the basic sentences in Arabic language, we will give some example of nominal sentences and verbal sentences in Arabic language.…”
Section: Introductionmentioning
confidence: 99%